Diagnostic Accuracy of the Aortic Dissection Detection Risk Score Plus D-Dimer for Acute Aortic Syndromes: The ADvISED Prospective Multicenter Study. Issue 3 (16th January 2018) - Nazerian, Peiman; Mueller, Christian; Soeiro, Alexandre de Matos; Leidel, Bernd A.; Salvadeo, Sibilla Anna Teresa; Giachino, Francesca; Vanni, Simone; Grimm, Karin; Oliveira, Múcio Tavares; Pivetta, Emanuele; Lupia, Enrico; Grifoni, Stefano; et al.
Abstract : Background: Acute aortic syndromes (AASs) are rare and severe cardiovascular emergencies with unspecific symptoms. For AASs, both misdiagnosis and overtesting are key concerns, and standardized diagnostic strategies may help physicians to balance these risks. D-dimer (DD) is highly sensitive for AAS but is inadequate as a stand-alone test. Integration of pretest probability assessment with DD testing is feasible, but the safety and efficiency of such a diagnostic strategy are currently unknown. Methods: In a multicenter prospective observational study involving 6 hospitals in 4 countries from 2014 to 2016, consecutive outpatients were eligible if they had ≥1 of the following: chest/abdominal/back pain, syncope, perfusion deficit, and if AAS was in the differential diagnosis. The tool for pretest probability assessment was the aortic dissection detection risk score (ADD-RS, 0–3) per current guidelines. DD was considered negative (DD−) if <500 ng/mL. Final case adjudication was based on conclusive diagnostic imaging, autopsy, surgery, or 14-day follow-up. Outcomes were the failure rate and efficiency of a diagnostic strategy for ruling out AAS in patients with ADD-RS=0/DD− or ADD-RS ⩽1/DD−. Results: A total of 1850 patients were analyzed. Of these, 438 patients (24%) had ADD-RS=0, 1071 patients (58%) had ADD-RS=1, and 341 patients (18%) had ADD-RS >1. Two hundred forty-one patients (13%) had AAS: 125 had type A aortic dissection, 53 had type B aortic dissection, 35 had intramural aortic hematoma, 18 had aortic rupture, and 10 had penetrating aortic ulcer. A positive DD test result had an overall sensitivity of 96.7% (95% confidence interval [CI], 93.6–98.6) and a specificity of 64% (95% CI, 61.6–66.4) for the diagnosis of AAS; 8 patients with AAS had DD−. In 294 patients with ADD-RS=0/DD−, 1 case of AAS was observed. This yielded a failure rate of 0.3% (95% CI, 0.1–1.9) and an efficiency of 15.9% (95% CI, 14.3–17.6) for the ADD-RS=0/DD− strategy. In 924 patients with ADD-RS ⩽1/DD−, 3 cases of AAS were observed. This yielded a failure rate of 0.3% (95% CI, 0.1–1) and an efficiency of 49.9% (95% CI, 47.7–52.2) for the ADD-RS ⩽1/DD− strategy. Conclusions: Integration of ADD-RS (either ADD-RS=0 or ADD-RS ⩽1) with DD may be considered to standardize diagnostic rule out of AAS. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02086136. Abstract : Supplemental Digital Content is available in the text.